Analysis Of Distribution Of Vitamins, Macro And Micro Elements Deficiency Among Children And Adolescents In Samarkand Region, According To Clinical Symptoms - Rakhimova Durdona Jurakulovna (Genius Journals, 2023)
Today, vitamin deficiency is one of the most common conditions among children. According to the results of the research, not only cases of monohypovitaminosis, but also cases of polyhypovitaminosis deficiency are increasing among children. [13,14,15,12,17,18]. At the same time, the increase in the number of diseases caused by vitamin deficiency shows the urgency of this problem and the need for urgent work to solve the problem. The organization of reasonable nutrition means that it is the main and important factor of improving the health status of children, ensuring harmony of mental and physical development [16,8,9,17,18,19,20]. We studied the nutritional status of 831 (414 boys and 417 girls) schoolchildren aged 7 to 17 years in cities and districts of Samarkand region. The results showed that 28.6% of schoolchildren had signs of vitamin deficiency, 9.8% had symptoms of monohypovitaminosis, and 18.8% had symptoms of polyhypovitaminosis
Keywords: children and teenagers; vitamins; macro and micro element